Co-creating the COMMUNICATE toolkit to support the communication of physical activity messages with adolescents in schools - Grady, Caera L.; Murtagh, Elaine; Verloigne, Maïté; McNally, Kathleen; García Bengoechea, Enrique; Ng, Kwok; Woods, Catherine B. (BioMed Central, 2026)
Background Communication campaigns within multi-component school-based interventions could improve knowledge and awareness about physical activity (PA) behavior. Guidance to implement such communication campaigns is lacking. This paper presents the co-creation and evaluation processes that led to the developent of the COMMUNICATE toolkit, which supports implementers to communicate PA messages.
Methods Students and teachers from secondary schools enrolled in the Active School Flag (ASF) program were invited to participate. To provide a nuanced perspective on the communication of PA, ASF program implementers (i.e., coordinating teacher and adolescent peer leaders) and receivers (i.e., staff and students not involved in ASF delivery), together known as co-creators, engaged in three rounds of co-creation workshops to share ideas, provide feedback, and refine the toolkit. Workshop data were collected via activity recording sheets; written raw materials were photographed and later transcribed verbatim to generate a dataset. Inductive thematic analysis was conducted to organize and describe the toolkit components. A multi-stakeholder research steering group (n=7) was established to design, facilitate, and evaluate the co-creation process. The toolkit was refined between rounds of workshops. Throughout the co-creation process, the facilitator reflected after each workshop to improve its’ participatory nature. After the final workshop, co-creators completed a process evaluation questionnaire. Additional consultations with experts were held to bridge the gap in expertise. A logic model was developed to understand the theory of change behind the toolkit.
Results Eight teachers and 38 students from four ASF schools participated in the co-creation workshops. All 14 aspects of the process evaluation were mainly positive (86.7-100%). Common reasons for negative responses included co-creators not engaging, too much moving around during workshops, teachers’ involvement, and working with strangers. The final version of the toolkit included resources for program implementers to i) raise awareness about PA and the program, ii) plan the promotion of PA, and iii) develop key communication skills.
Conclusions The COMMUNICATE toolkit, informed by multi-stakeholder voices, emphasizes a multi-level, multi-stakeholder approach to communicating PA messages with adolescents in schools. It provides tools and resources for program implementers to improve communication efforts. The COMMUNICATE toolkit could be adapted to other peer-led school-based programs.